Nota dos editores - Viana Diniz de Freitas, Roberto; Mont'Alverne Barreto Lima, Martonio; Cavalcanti Ramos Machado, Raquel (Suffragium - Revista Científica do Tribunal Regional Eleitoral do Ceará, 2021)
Nota dos editores